Molecular Attributes Associated With Refolding of Inclusion Body Proteins Using the Freeze–Thaw Method - Singhvi, Priyank; Verma, Juhi; Panwar, Neha; Wani, Tabiya Qayoom; Singh, Akansha; Qudratullah, Md.; Chakraborty, Arnab; Saneja, Ankit; Sarkar, Debi P.; Panda, Amulya K. (Frontiers in Microbiology, 2021)
Structure-function understanding of inclusion bodies (IBs) in the last two decades have led to the development of several mild solubilization buffers for improved recovery of bioactive proteins. Recently developed freeze-thaw based inclusion body proteins solubilization method has received a great deal of attention due to its simplicity and cost-effectiveness. The present report investigates the reproducibility, efficiency and plausible mechanism of the freeze-thaw based IBs solubilization. Percentage recovery of functionally active protein species of human growth hormone (hGH) and L-asparaginase from their IBs in E. coli and the quality attributes associated with freeze-thaw based solubilization method was analyzed in detail. The overall yield of purified hGH and L-asparaginase protein was found to be around 14% and 25% respectively. Both the purified proteins had functionally active species lower than that observed with commercial proteins. Biophysical and biochemical analysis revealed that the formation of soluble aggregates was a major limitation in the case of tough IB protein like hGH. On the other hand, the destabilization of soft IB protein like L-asparaginase led to the poor recovery of functionally active protein species. Our study provides an insight into the advantages, disadvantages and molecular-structural information associated with freeze-thaw based solubilization method.